Inventors at work the minds and motivation behind modern inventions - Stern, Brett (Apress, 2025)
Inventors at Work: The Minds and Motivation Behind Modern Inventions is a collection of interviews with inventors of famous products, innovations, and technologies that have made life easier or even changed the way we live. All of these scientists, engineers, wild-eyed geniuses, and amateur technologists have dedicated their lives to the pursuit of that singular Eureka! moment in their laboratories or garages. Each has altered the modern world as we know it in some significant way. The conversations will show budding tinkerers, professional inventors,  educators, and onlookers how the top minds in the field come up with ideas and manage the first steps of inspiration, how they experiment productively, how they “sell” ideas to others and secure funding, how they execute the final product, and how they commercialize and protect their work. All inventors will learn from these conversations, whether they are exploring new chemical compounds in million-dollar labs or perfecting a household gadget or toy in a basement workshop. Author Brett Stern, an inventor himself, explores with each inventor the nature of creativity and intuition, the skill set needed, and the force, motivation, or desire that must be summoned to spend endless hours searching for an answer to a question that no one else has asked or solving a problem most think has no solution. The book is required reading for all technical and creative individuals to better understand the innovation process and the logistics of following through on an idea that has the potential to change society. This book offers: Interviews with inventors of world-changing products and technologies An outline of the steps required in the creative/inventing process whether the goal is a civilization-changing process or a device meant to impress friends and family and perhaps earn license fees.An instructive overview of how to solve problems in innovation—and how to use failures as stepping stones to successful inventions.